The Use of the Village Financial System (Siskeudes) Application to Increase the Accountability of Village Financial Reports - Sulfianty Sulfianty; Agus Baku; Susanto Nohi; Purnama Sari; Kartini Muslimin (Journal of Creative Power and Ambition (JCPA), 2026)
The Use of the Village Financial System (Siskeudes) Application to Increase the Accountability of Village Financial Reports